DIGITIZATION AND DIGITAL PRESERVATION ACTIVITIES AND INITIATIVES AT THE ADDIS ABABA UNIVERSITY: TOWARDS INSTITUTIONAL DIGITIZATION AND DIGITAL PRESERVATION STRATEGY - Wordofa, Teklemichael T. (My University, 2012)
Addis Ababa University (AAU), the leading academic and research institution in Ethiopia, produces a tremendous amount of research output. Theses and dissertations, scholarly journals, proceedings and staff/discussion papers are among the major items. The print materials are available in different units of the University. Some units (schools and faculties) are planning to conduct mass digitization on some print collections of indigenous knowledge. Others have already started digitization activities on a smaller scale. However, digitization is a resource intensive and costly activity and hence requires a strategic approach. On the other hand, the practice of collecting and preserving “born digital” materials at the AAU is in its infancy. This has influenced the development of digital library infrastructure (for example institutional repositories) that provides access and increases the visibility of digitally born research materials to researchers. This paper examines the digitization activities and practice for managing born digital research materials, and suggests a strategic approach to digitization for the AAU. It brings together all relevant units of the University towards the establishment of a centre of digitization with a clearly defined digitization and digital preservation strategy.
Keywords: digitization strategy, digital preservation, Digital Projects Centre, Addis Ababa University